2019
DOI: 10.1016/j.ejmech.2019.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Sequence modification of heptapeptide selected by phage display as homing device for HT-29 colon cancer cells to improve the anti-tumour activity of drug delivery systems

Abstract: Development of peptide-based conjugates for targeted tumour therapy is a current research topic providing new possibilities in cancer treatment. In this study, VHLGYAT heptapeptide selected by phage display technique for HT-29 human colon cancer was investigated as homing peptide for drug delivery. Daunomycin was conjugated to the N-terminus of the peptide directly or through Cathepsin B cleavable spacers. Conjugates showed moderate in vitro cytostatic effect. Therefore, sequence modifications were performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
3
14
0
1
Order By: Relevance
“…On the contrary, we obtained relatively high IC 50 and relative potency values in case of MRC-5 cells, which suggested that the conjugates are highly tumor selective, except for PANC-1 cells, where the IC 50 value of the free Dau was also substantially higher than for the other cancer cell lines. Higher values of relative potency indicate a loss of potency of the conjugates with respect to free Dau [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, we obtained relatively high IC 50 and relative potency values in case of MRC-5 cells, which suggested that the conjugates are highly tumor selective, except for PANC-1 cells, where the IC 50 value of the free Dau was also substantially higher than for the other cancer cell lines. Higher values of relative potency indicate a loss of potency of the conjugates with respect to free Dau [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of synthetic therapeutics have been used which target receptors, and hence revealed a significant tumor growth inhibition in vitro and in vivo. Thus, HT-29 human colon tumors were implanted to the intestine of immunodeficient SCID mice [75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…Daunorubicin was used for the development of a large number of peptide-drug conjugates in our laboratory that showed efficient antitumor activity not only in vitro, but also in vivo. 4,5 Daunorubicin consists of an anthraquinone aglycon part and a daunosamine sugar moiety linked to the tetracycline by a glycosidic bond. Due to the complex structure of PDCs, tandem mass spectrometry is an indispensable tool for verification of the structure and purity of synthetic products.…”
mentioning
confidence: 99%
“…Mass spectrometry is widely used to determine the release of drugs from PDCs, and to identify their metabolites. [4][5][6][7][8] In the case of anthracycline containing PDCs, however, mass spectrometric analysis is hindered by the degradation of the compounds during electrospray ionization (ESI). ESI is a soft ionization technique, producing intact, singly or multiply protonated molecules from peptides.…”
mentioning
confidence: 99%